Floristic differentiation of a deciduous seasonal forest tree stratum, Jaguari, RS, Brazil - Andrzejewski, Camila (2019)
This study aims at determining and differentiating the floristic groups of a Deciduous Seasonal Forest’s arboreal component, located on the ridge of the Southern Plateau, in Southern Brazil. Individuals with diameter at breast height ≥ 5.0 cm were sampled in sixty-two plots measuring 10 m × 10 m, which were systematically installed in the forest. Three floristic groups were found: Middle Stage, including 54 species, with Casearia sylvestris as an indicator species; Advanced Stage, with 38 species and Pilocarpus pennatifolius as the indicator species; and Altered Forest, with 27 species and Apuleia leiocarpa, Helietta apiculata, and Machaerium paraguariense as indicator species. A higher proportion of climax light-demanding individuals was reported in the Middle Stage and Altered Forest groups, contrasting with the Advanced Stage group, in which climax shade-tolerant species were predominant. In addition, the groups were differentiated according to their dispersion strategy, with specific syndromes occurring in each group (Middle Stage: zoochory; Advanced Stage: autochory; Altered Forest: anemochory).